Gangguan Terlambat Berbicara Pada Anak Usia Dini (Speech Delay) - Jahra Wilya Wibowo; Heru Pratikno (Institut Nalanda, 2025)
Speech delay is one of the speech developmental disorders in children. The stages of a child's speech development are crucial to facilitate their interaction with others. However, currently, there are several children at an early age who are diagnosed with speech delay. This study aims to identify the factors that cause speech delay in preschool children and the solutions to this issue. The research method used is a descriptive qualitative approach. Data collection techniques include literature review, observation, and interviews. The discussion explains the findings from the collected data, revealing several factors that contribute to speech delay in young children. In this regard, the primary solution lies with the parents.